Analysis of the Influence of RGEC on Company Value in the Banking Financial Sector for the Period 2020 - 2024 - Larasati, Fitria; Hendayana, Yana (Dinasti International Journal of Economics, Finance & Accounting, 2026)
This study aims to analyze the effect of RGEC (Risk Profile, Good Corporate Governance, Earnings, and Capital) on company value as measured by Price to Book Value (PBV) in the Indonesian banking financial sector during the 2020–2024 period. The research approach used is quantitative with descriptive and verification methods, and uses panel data regression to analyze the effect of each variable. The sample consists of 25 banking companies selected based on purposive sampling. The t-test results indicate that the variables NPL, ROA, and CAR have a significant effect on PBV, while GCG has no significant effect. Meanwhile, the F-test shows that all four variables simultaneously have a significant effect on PBV. These results indicate that company management needs to pay attention to credit risk, profitability, and capital adequacy in an integrated manner to increase company value. This study provides implications for investors and management in making investment decisions and strategies to increase company value.